Effect of vegetable fat on the texture, colour and sensory properties of Macedonian white brined cheese - Erhan Sulejmani; Lavdrim Beqiri; Riste Popeski-Dimovski (Mljekarstvo)
This study aimed to investigate the influence of substitution of milk fat with palm fat on the composition, yield and technological quality of White cheese, a Macedonian traditional cheese. In this study, full-fat white brined cheese was used as a control sample (WC), while experimental cheeses were prepared from cow milk with vegetable fat (WV) addition and low-fat cheese (WL), respectively. The cheeses have been analysed for physicochemical (acidity, pH, fat, fat acidity, protein), instrumental texture and colour properties (L, a, b) as well as the sensory properties after 1, 20 and 60 days. WV cheeses showed a significantly (P<0.05) lower degree of pH and higher titratable acidity than the WC and WL cheese samples. Cheese that contained vegetable fat showed lower degrees of lipolysis, as assessed by the acid-degree value and received significantly (P<0.05) better appearance, highest hardness value (5226.98 N) and cheese yield scores compared to other samples.